2021
DOI: 10.1088/1361-6498/ac20ae
|View full text |Cite
|
Sign up to set email alerts
|

No more glowing in the dark: how deep learning improves exposure date estimation in thermoluminescence dosimetry

Abstract: The time- or temperature-resolved detector signal from a thermoluminescence dosimeter can reveal additional information about circumstances of an exposure to ionising irradiation. We present studies using deep neural networks to estimate the date of a single irradiation with 12 mSv within a monitoring interval of 42 days from glow curves of novel TL-DOS personal dosimeters developed by the Materialprüfungsamt NRW in cooperation with TU Dortmund University. Using a deep convolutional network, the irradiation da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, researchers have explored the feasibility of using ML algorithms for identifying anomalous GCs, to study the characteristics of TL emission and for the estimation of elapsed time after exposure [3,[8][9][10][11][12][13][14][15]. As mentioned earlier, we demonstrated the effectiveness of ML algorithms in identifying abnormal GCs and classifying them based on the associated abnormalities [3].…”
Section: Introductionmentioning
confidence: 53%
“…Recently, researchers have explored the feasibility of using ML algorithms for identifying anomalous GCs, to study the characteristics of TL emission and for the estimation of elapsed time after exposure [3,[8][9][10][11][12][13][14][15]. As mentioned earlier, we demonstrated the effectiveness of ML algorithms in identifying abnormal GCs and classifying them based on the associated abnormalities [3].…”
Section: Introductionmentioning
confidence: 53%
“…Finally, a look at the future of research cannot ignore the role of the increasing opportunities offered by the field of Artificial Intelligence. For instance, deep learning and computer vision are increasingly being used in many sectors of dosimetry and radiation protection [143] and a few preliminary experiences in EPR and thermoluminescence dosimetry [144,145]. From these future scenarios, it is clear that computation will become more and more relevant to experimental dosimetry.…”
Section: Future Research Of Computational Modelling In Rdmentioning
confidence: 99%
“…The official dose monitoring of workers is performed with passive dosimeters and active dosimeters are carried as a secondary device. Mentzel demonstrated that a NN trained on the glow curves of passive dosimeter can assess without the active dosimeter the date of a single high-dose irradiation; the method could be "extended to a wide range of additional insights into irradiation scenarios" (Mentzel, 2021).…”
Section: Regulationmentioning
confidence: 99%